Juridical review of maritime boundary between Australia-Timor Leste and Indonesia - Muhammad Al Imran Zani R. (Scientific Journal of Gdynia Maritime University, 2020)
The sea area has a strategic position, so it is necessary to regulate the boundaries of international maritime zones to prevent seizure of waters between countries of the world. The purpose of this study was to legally analyze the maritime boundary between Australia-East Timor and Indonesia. This research method uses descriptive-qualitative analysis, normative juridical approach, and collects primary and secondary legal materials. Juridically, Indonesia has borders with several countries including Australia. With regard to sea areas or waters, what can be used as a legal basis is the 1982 International Ocean Law Conference held by the United Nations through the United Conference on The Law of the Sea (UNCLOS) held in Jamaica. The maritime boundary between Indonesia and Australia has been agreed in the Indonesia-Australia maritime boundary agreement at the Geneva Convention 1958. With this agreement, the continental shelf boundary has been agreed at a depth of 200 m and can be exploited.